Menebus Kesalahan, Meraih Hak: Kisah Narapidana Narkotika di Balik Jeruji - Muhammad Fadli Muslimin; Iswandy Rani Saputra; Amir Amir (Jurnal Litigasi Amsir, 2024)
This research aims to determine the implementation of fulfilling the rights of prisoners who abuse narcotics in the Class IIB Pinrang Detention Center based on UUD Number 22 of 2022 concerning Corrections and the Obstacles faced by the IIB Pinrang Detention Center in implementing the fulfilment of prisoners' rights. This research uses a normative-empirical type of legal research. The research results show that the Class IIB Pinrang Detention Center has fulfilled prisoners' rights following the rules in Article 9 of Law Number 22 of 2022 concerning Corrections. These efforts are implemented through coaching activities as well as coaching social activities, health education, and job guidance. This is also done by providing service innovation and supporting facilities and infrastructure. The obstacles faced in implementing the fulfilment of prisoners' rights at the Pinrang Class IIB Detention Center are that religious activities require preachers so that prisoners are better than before, information services that must be socialized to understand better the terms and conditions of getting remission, getting newer reading materials. to increase interest in reading and for inmates who have families far from remote areas to make it easier to visit the class IIB Pinrang prison.